Pemanfaatan Trichoderma Harzianum Pada Kompos Dan Fungi Mikoriza Arbuskula Terhadap Pertumbuhan Rumput Kumpai - Yusuf, Dwiky Andryawan; Adriani, Adriani; Syafria, Hardi; Azizah, Azizah; Hidayat, Rahmat; Lestari, Wenni Meika (Politeknik Pertanian Bogor, 2025)
The conversion of agricultural land reduces the available forage cultivation areas, making post-coal mining land a potential alternative. However, its poor soil fertility requires specific treatments to enhance nutrient content. This study evaluates the effect of Trichoderma harzianum (TH) on compost quality and the impact of Arbuscular Mycorrhizal Fungi (AMF) on the growth of Hymenachne amplexicaulis (Rudge) Ness (kumpai grass). The first phase analyzed compost pH, N, P, K, C, and C/N ratio with treatments: P0= (control: 40% cow manure, 35% empty palm bunches, 20% palm fronds, 4% rice bran, 1% urea), P1 (P0 + 2% TH), P2 (P0 + 4% TH), and P3 (P0 + 6% TH). The second phase examined using a factorial design (3×2) of the effects of compost (A0=0 g, A1=12 g, and A2=24 g) and AMF (B0 =0 gr/pot, B1= 20gr/pot). Results showed that TH increased compost C, N, P, and C/N ratio but did not affect pH and K (P>0.05). Compost and AMF interacted to improve Kumpai dry matter yield, while AMF alone increased the number of tillers. Plant height and root dry matter were unaffected. The best compost quality was obtained with 6% TH, while 20 g AMF per pot maximized tiller production. The optimal combination was A2B1 (24 g compost + 20 g AMF per pot), indicating a significant interaction between TH and AMF in enhancing kumpai grass biomass. These findings highlight the potential of integrating compost and AMF to improve post-mining land fertility and forage production.